The identification of misconceptions in visual learners based on the certainty of response index (CRI) in solving numeracy problems in algebra - Zidni Elma; Nurcholif Diah Sri Lestari; Ervin Oktavianingtyas; Dinawati Trapsilasiwi; Lela Nur Safrida (State Islamic University of North Sumatra, 2025)
This study aims to identify and analyze the misconceptions encountered by students with a visual learning style in solving algebraic numeracy problems using the Certainty of Response Index (CRI) method. The research was conducted with eighth-grade students at SMPN 4 Jember who had previously studied equations and inequalities. A qualitative descriptive approach was employed, with data collected through questionnaires, tests, and interviews. To ensure data validity, member checks were conducted. The findings reveal three distinct types of misconceptions: theoretical, correlational, and classificational. Students with a visual learning style exhibited theoretical misconceptions, including misunderstandings of variable concepts and PtLSV (Pertidaksamaan Linear Satu Variabel - One-variable Linear Inequality) framework, errors in algebraic operation principles, and flawed reasoning when responding to problems. Additionally, correlational misconceptions were identified, such as difficulties in translating given information into mathematical expressions and errors in representing concepts across different mathematical formats. These misconceptions primarily stem from students' incomplete or inaccurate prior knowledge, limited conceptual understanding, and associative thinking patterns. To mitigate these issues, educators are encouraged to assess students' initial comprehension through diagnostic testing, enabling early identification and correction of misconceptions. Addressing these misunderstandings at an early stage can prevent further cognitive obstacles when students engage with more complex mathematical concepts.